Biographical Work of Parents of Children with Non-Normative Sexual Orientation and/or Gender Identity - Katarzyna Gajek (Qualitative Sociology Review, 2024)
This paper aims to reconstruct the biographical work (Corbin and Strauss) undertaken by parents of non-normative people. The initiating event of biographical work is the disclosure of a non-normative sexual orientation and/or gender identity by the child. For many parents, this is an event that causes a breakdown of previous schemes of action, a gradual loss of control, and suffering.